Application of Problem-Based Learning (PBL) Learning Model to Improve Student Learning Outcomes in Arithmetic Row Material Class XI SMAN 6 Southwest Aceh - Khahona Afrinia; Baidullah Baidullah (Publikasi Indonesia, 2024)
In this era of globalization, the low mathematics learning outcomes of students at the high school level, especially at SMAN 6 Aceh Barat South, are caused by the fact that in the learning process, teachers only focus on using less competent methods, so students get bored easily. The purpose of this study is to determine the completeness of student learning outcomes through Problem-Based Learning on Arithmetic Rows and Series Materials. This research is classified as a classroom action research that is carried out in two research cycles. In each research cycle, there are 4 stages consisting of planning, implementation, observation, and reflection stages. Data collection in the study was carried out using the test method. The data obtained in the study were then analyzed by analytical descriptive analysis techniques and qualitative descriptive analysis. The results of the study showed that the average student learning outcome in the pretest was 65.4 and increased in the post-test, which was 70.9. Based on these results, it can be seen that there is an increase in student learning outcomes in each cycle. Therefore, it can be concluded that the application of the problem-based learning model can significantly improve the mathematics learning outcomes of high school students.